Answer:
4a) 3b+14; f=-5
3(-5)+14
-15+14
=-1
4b) 3b+14; f=-3
3(-3)+14
-9+14
=5
4c) 3b+14; f=0
3(0)+14
0+14
=14
4d) 3b+14; f=4
3(4)+14
12+14
=26
5a) 6.75-6v; v=1
6.75-6(1)
6.75-6
=0.75
5b) 6.75-6v; v=2
6.75-6(2)
6.75-12
=-5.25
5c) 6.75-6v; v=5
6.75-6(5)
6.75-30
=-23.25
5d) 6.75-6v; v=-3.25
6.75-6(-3.25)
6.75+19.5
=26.25
6a) f/4 +3f; f=4
4/4 +3(4)
1+12
=13
6b) f/4+3f; f=8
8/4+3(8)
2+24
=26
6c) f/4+3f; f=-12
-12/4+3(-12)
-3-36
=-39
6d) f/4+3f; f=-1
-1/4+3(-1)
=-1/4+-3
Explanation:
Plug in the value into the equations and solve.
hope this helps :)